Comparative study on indoor environmental quality of green office buildings with different levels of energy use intensity. (15th January 2020) - Geng, Yang; Lin, Borong; Zhu, Yingxin
Abstract: Energy use intensity (EUI) and indoor environmental quality (IEQ) are two key features for evaluating the operating performance of green buildings. However, few researchers have investigated the relationship between the EUI and IEQ in green buildings. In this study, 20 green office buildings from the hot-summer-cold-winter (HSCW) climate zone in China were chosen to investigate their energy use and conduct long-term environmental measurements and occupant satisfaction surveys. Based on over three million sets of environmental data and 1, 756 survey samples, IEQ performances (including the thermal comfort, air quality and visual environment) of low- and high-EUI buildings were compared. The results indicate that high-EUI buildings exhibited a significantly better thermal environment, compared to low-EUI buildings. Regarding air quality and visual environment, the two groups did not exhibit huge differences, and their mean levels conformed to the local standard. The subjective surveys led to an inconsistent conclusion: the occupants in high-EUI buildings were less satisfied with the IEQ than those in low-EUI buildings, except for visual environment. The possible underlying reason can be the different levels of environmental control. Furthermore, the detailed relationship between energy use and thermal environment was studied. While green office buildings consume more energy and thus guarantee minimal requirements for thermal comfort, they also waste more energy owing to overcooling or overheating. Finally, an indicator-Environmental Energy Efficiency (EEE)-was introduced and applied to evaluate the comprehensive performance of the energy consumption and IEQ of buildings. Highlights: The IEQ of 20 green office buildings with different EUI levels was compared. High-EUI buildings did not always exhibit a better IEQ performance than low-EUI buildings. The detailed relationship between the energy and thermal environment was studied. The comprehensive evaluation indicator 'Environmental Energy Efficiency' was introduced.